The Influencing Factors on the Effectiveness of Foundation Training Programs: A Case Study of the Health Cadre Service in Bangladesh - Rahman, Mohammad Ziaur; Kumarasamy, Mokana A/P Muthu; Bhuiyan, Abul Bashar (International Journal of Business and Management Future, 2019)
The research has been conducted to understand the training effectiveness where health professional participates for training who work under the Bangladesh Government. The research used the Kirkpatrick model. The paper has collected data form, 323 participants. The research measured the training effectiveness using survey questions. The multiple regression techniques have used to conduct analysis of the collected data. The findings of the research revealed that the training effectiveness has been affected significant positively by training motivation, trainer qualification, and training design. Moreover, the training environment does not have significant role on the impacting of the training effectiveness respectively. The study has specific recommendations based on the above findings as the bench mark to improve the effectiveness training in Bangladesh and the regions.